The Phenomenon of Ostalgie in Czech and German Television Series - Kateřina Kočárková (Kulturní Studia)
Ostalgia – a nostalgic longing for aspects of life in former socialist regimes – permeates various domains of social and cultural life, including fashion, consumer goods, music, and popular media. This study explores ostalgia on the cultural level, focusing in particular on contemporary television series. The theoretical framework draws on concepts of collective memory and the culture of remembrance, with special attention to the material dimension of memory. Ostalgic narratives frequently foreground everyday objects, evoking a sense of temporal dislocation wherein the past can only be accessed through selective remembrance. This phenomenon is discussed in relation to the notion of the ‚memory of things‘, as formulated by Jan Assmann and further developed by Arjun Appadurai. Material artefacts from the socialist era serve as vessels of memory, enabling individuals to retrieve personal and collective pasts. The analysis centres on two Czech series – Vyprávěj (Tell Me About It) and Svět pod hlavou (World Under the Head) – and two German productions – Ku’damm (Kurfürstendamm) and Deutschland 83 (Germany 83) – offering a comparative perspective on how ostalgia is represented and mediated through televised storytelling in post-socialist contexts.